Allergen hybrids – next generation vaccines for Fagales pollen immunotherapy. Issue 3 (March 2014) - Pichler, U.; Hauser, M.; Hofer, H.; Himly, M.; Hoflehner, E.; Steiner, M.; Mutschlechner, S.; Hufnagl, K.; Ebner, C.; Mari, A.; Briza, P.; Bohle, B.; et al.
Summary Background Trees belonging to the order of Fagales show a distinct geographical distribution. While alder and birch are endemic in the temperate zones of the Northern Hemisphere, hazel, hornbeam and oak prefer a warmer climate. However, specific immunotherapy of Fagales pollen‐allergic patients is mainly performed using birch pollen extracts, thus limiting the success of this intervention in birch‐free areas. Objectives T cells are considered key players in the modification of an allergic immune response during specific immunotherapy (SIT), therefore we thought to combine linear T cell epitope‐containing stretches of the five most important Fagales allergens from birch, hazel, alder, oak and hornbeam resulting in a Fagales pollen hybrid (FPH) molecule applicable for SIT. Methods A Fagales pollen hybrid was generated by PCR‐based recombination of low IgE‐binding allergen epitopes. Moreover, a structural‐variant FPH4 was calculated by in silico mutagenesis, rendering the protein unable to adopt the Bet v 1‐like fold. Both molecules were produced in Escherichia coli, characterized physico‐chemically as well as immunologically, and tested in mouse models of allergic sensitization as well as allergy prophylaxis. Results Using spectroscopic analyses, both proteins were monomeric, and the secondary structure elements of FPH resemble the ones typical for Bet v 1‐like proteins, whereas FPH4 showed increased amounts of unordered structure. Both molecules displayed reduced binding capacities of Bet v 1‐specific IgE antibodies. However, in a mouse model, the proteins were able to induce high IgG titres cross‐reactive with all parental allergens. Moreover, prophylactic treatment with the hybrid proteins prevented pollen extract‐induced allergic lung inflammation in vivo. Conclusion The hybrid molecules showed a more efficient uptake and processing by dendritic cells resulting in a modified T cell response. The proteins had a lower IgE‐binding capacity compared with the parental allergens, thus the high safety profile and increased efficacy emphasize clinical application for the treatment of Fagales multi‐sensitization.